Permeability Enhancing and Chemotactic Activities of Lower Molecular Weight Degradation Products of Human Fibrinogen - Sueishi, Katsuo; Nanno, Shigeru; Tanaka, Kenzo (Thrombosis and Haemostasis, 1981)
Fibrinogen degradation products were investigated for leukocyte chemotactic activity and for enhancement of vascular permeability. Both activities increased progressively with plasmin digestion of fibrinogen. Active fragments were partially purified from 24 hr-plasmin digests. Molecular weights of the permeability increasing and chemotactic activity fractions were 25,000-15,000 and 25,000 respectively. Both fractions had much higher activities than the fragment X, Y, D or E. Electron microscopic observation of the small blood vessels in rabbit skin correlated increased permeability with the formation of characteristic gaps between adjoining endothelial cells and their contraction.These findings suggest that lower molecular weight degradation products of fibrinogen may be influential in contributing to granulocytic infiltration and enhanced permeability in lesions characterized by deposits of fibrin and/or fibrinogen.
Keywords: Lower molecular weight FDP; Permeability; Chemotactic activity